Big data technologies and applications : 8th International Conference, BDTA 2017, Gwangju, South Korea, November 23-24, 2017, Proceedings /: 8th International Conference, BDTA 2017, Gwangju, South Korea, November 23-24, 2017, Proceedings. (2018) - Unknown
No abstract available